Mindfulness of Breathing in the Samyukta-agama - Anālayo, Ven. (Buddhist Studies Review, 2007)
The present article supplies an annotated translation of the sixteenfold instructions on mindfulness of breathing in the Chinese Samyukta-agama. These instructions show how mindfulness of breathing fulfi ls the four satipatthanas and leads to the development of the seven bojjhangas, thereby leading to knowledge and liberation. The translation is followed by a comparison with its Pali counterpart, the Ananda-sutta in the Samyutta-nikaya.